Impact of Infant Massage on Weight Gain: A Study in Banjar District, South Kalimantan - Adha Aprilea, Noor; Sofia, Norlaila; Rohmah Prihatanti, Nur; Rusmilawaty, Rusmilawaty (Jurnal Keterapian Fisik, 2024)
Background: Underweight in children under five is still a significant health problem in many parts of the world, especially in developing countries. One such intervention that has gained cultural significance is infant massage, a traditional practice that promotes relaxation, improves digestion, and enhances weight gain. This study seeks to evaluate the impact of infant massage on weight gain in infants under 24 months within Banjar Regency, a region where undernutrition presents a significant public health issue. While infant massage is traditionally practiced and believed to benefit infant health, its effectiveness remains debatable. Methods: A quasi-experimental design with a control group involving 51 mother-infant pairs was employed. Participants were divided into an intervention group (n=17) that received infant massage training and performed it over three months and a control group (n=34) that received no such intervention. This research uses an observation form instrument. Infant weight gain was the primary outcome measure, with data analyzed using independent sample t-tests to assess differences between the two groups. Results: No statistically significant difference was found in weight gain between the intervention and control groups (t = -0.415, p = 0.680). However, descriptive data revealed that 88.2% of infants in the intervention group experienced weight gain compared to 85.3% in the control group, indicating a potential trend toward positive effects of infant massage. Conclusion: Despite the lack of statistical significance, the observed trend suggests potential benefits of infant massage. Further research with larger sample sizes and longer durations is recommended.